Mindset de crescimento como modificador do potencial empreendedor: um estudo experimental em Startups - Frederico Leocadio Ferreira (2019)
Growth Mindset is an attitude toward development and continuous learning. Such an attitude can be strengthened and developed in individuals to in turn these individuals can contribute with the organization who belongs in a systemic way. In contrast, individuals can assume a defensive attitude focusing in their own performance (Performance Fixed Mindset). In turn, these individuals avoid challenging tasks and involvement with learning and changes (Blocker Fixed Mindset). These dissertation applied the treatment to potentiate the Growth Mindset using the design of Blackwell et al. (2007) e Luthans et al. (2006), in order to observe possible changes on the level of Internal Entrepreneurial Potential (PEI) of individuals in Startups. PEI is the entrepreneurial potential present in individuals within an organization without these individuals having the desire to open their own business. These individuals with high levels of PEI invest in new projects, products, or process improvement within their current organization. The experiment were applied to Startups belonging to the San Pedro Valley, a Startup conglomerate of Belo Horizonte with over 250 Startups. The treatment took place in a section (one-shot) due to the limited time of the Startups involved. The duration was approximately 3 hours and the sample was 108 test units. Questionnaires were applied after the interventions to measure the results: (i) The Mindset questionnaire composed of 13 questions; (ii) the PEI composed of 52 questions; (iii) the 5 major personality traits of 17 questions. In order to measure the relationship between the variables Mindset, PEI and the five major traits mentioned above, the research used structural equation modeling through a confirmatory factorial analysis, aiming to infer a causal relationship through experimental design. Through the experiment it can be seen that the proposed treatment increased the positive relationship between the growth Mindset and the IEP, as well as the relationship between the performance mindset and the IEP. For future research, it is suggested (i) the application in larger samples and in different contexts and niches for a greater generalization of the results; (ii) the application of the treatment in a longitudinal way, to verify if the results will be persistent or momentary; (iii) test this relationship with other consequents, such as absorptive capacity, organizational learning and; (iv) to delve deeper into the antecedents of Mindset in a causal / longitudinal way.